Work-in-Progress: Integrating WebAssembly into Service-Oriented Architectures for Edge Systems - Kreutzer, Marius; Seidler, Maximilian; Pazmino, Victor Betancourt; Becker, Jürgen (Proceedings of the International Conference on Embedded Software, 2024)
Complex edge systems are often structured with service-oriented architectures. Different communications stacks such as MQTT, DDS, or Zenoh are used, hindering reuse of service implementations across systems. One emerging solution for deploying such services is WebAssembly, which enables platform-independent, secure, and low-overhead execution. We propose a concept for integrating Web-Assembly modules into microservice-based architectures using a specialized runtime. This runtime manages the communication between the WebAssembly module and other parts of the system. The runtime for integration of WebAssembly addresses the challenge of reusing service implementations across systems with different communication protocols. At the same time, this provides isolated, safe and secure execution. Both capabilities are central to service-oriented edge systems.
Keywords: WebAssembly; service-oriented architecture; edge computing